Physical urticarias and cholinergic urticaria - Abajian, Marina; Schoepke, Nicole; Altrichter, Sabine; Zuberbier, Torsten; Zuberbier, H C Torsten; Maurer, Marcus (Immunology and allergy clinics of North America, 2014)
Physical urticarias are a unique subgroup of chronic urticaria in which urticarial responses can be reproducibly induced by different specific physical stimuli acting on the skin. These conditions include urticaria factitia/symptomatic dermographism, delayed pressure urticaria, cold contact urticaria, heat contact urticaria, solar urticaria, and vibratory urticaria/angioedema. Physical urticarias and cholinergic urticarias are diagnosed based on the patients' history and provocation tests including trigger threshold testing where possible. Treatment is mainly symptomatic. Many patients benefit from avoiding eliciting triggers, and desensitization to these triggers can be helpful in some physical urticarias and in cholinergic urticaria.